Effect of fishmeal and trash fish-based diets on the fry, Lates calcarifer (Bloch) reared in ponds and indoor aquaria - Marasigan, Evelyn S. Tubongbanua (Iloilo College of Fisheries, University of the Philippines in the Visayas, 1988)
Two major protein sources, fish meal and trash fish were incorporated into five dietary treatments were tested in Trial A as follows : I- dry pelleted fishmeal-based diet ; II - moist fishmeal-based diet ; III - moist raw trashfish-based diet ; IV - moist pasteurized trashfish-based diet, and V - moist sun-dried trashfish-based diet.Forty-five day old fry were gradually weaned from hatchery diet consisting of minced raw trash fish and artemiasalinanuplii to thefive diets for seven days. After weaning, the fish with a men weight of 0.36 g were stocked in 100m2 earthen ponds at a rate of 50 fish/pond and fed with the five test diets for 114 daysculture period. Significant differences (P>0.05) in fish biomass were obtained among treatments. The pasteurized trash fish diet (Treatment IV) resulted to better biomass and feedconversion values in seabass cultured in ponds compared to other trash fish diets (Treatment III and V) and fishmeal-based diets (Treatment I and II). This indicated the potential ofpasteurized trash fish based-diet on the culture of seabass, although there are possibilities that production and fed conversion efficiency of pelleted fishmeal based-diets can be improved. On the basis of the results in Trial A, Trial B was undertaken to compare the effects of various sources of protein on the growth and survival of seabass fry as follows : Japanesefishmeal-based diet (Treatment I), local fishmeal-based diet (Treatment II), pasteurized trash fish + Treatment I at 1:1 ratio (Treatment III), and pasteurized trash fish onlt ( Treatment IV). Twenty-one day old seabass fry were reared and fed with the four dietary treatments for 24 days in indoor aquaria provided with recirculating water system. The effects of experimentaldietary treatments were ranked using the Vector Analysis with respect to growth increment, fish biomass and survival data. Results of analysis showed the following : first, Treatment I ;second,Treatment III and IV, and third, Treatment II. These results indicated that using formulated diet in rearing seabass fry, the performance of the diet with fish meal as the major protein source in terms of growth and survival of seabass fry would vary even if their crude protein content were similar. This suggests that the effects of artificial diets on the growth and survival of seabass fry depends upon the source of protein.
Thesis (M. S. Fisheries) - University of the Philippines in the Visayas, March 1988.
Keywords: Seabass; Giant perch